ab/d + c = e for d
I know this is a literal equation because we are asked to solve for a variable in terms of another variable
Subtract c from each side to isolate the d term:
ab/d + c - c = e - c
Cancel the c's on the left side and we get:
ab/d = e - c
Cross multiply:
ab = d(e - c)
Divide each side of the equation by (e - c):
ab/(e - c)= d(e - c)/(e - c)
Cancel the (e - c) on the right side, and we get:
d = ab/(e - c)
I know this is a literal equation because we are asked to solve for a variable in terms of another variable
Subtract c from each side to isolate the d term:
ab/d + c - c = e - c
Cancel the c's on the left side and we get:
ab/d = e - c
Cross multiply:
ab = d(e - c)
Divide each side of the equation by (e - c):
ab/(e - c)= d(e - c)/(e - c)
Cancel the (e - c) on the right side, and we get:
d = ab/(e - c)